Chronic immobilization stress occludes in vivo cortical activation in an animal model of panic induced by carbon dioxide inhalation - Rahman, Mohammed Mostafizur; Kerskens, Christian M.; Chattarji, Sumantra; O'Mara, Shane M. (Frontiers in Behavioral Neuroscience, 2014)
Breathing high concentrations of carbon dioxide (CO2) can trigger panic and anxiety in humans. CO2 inhalation has been hypothesized to activate neural systems similar to those underlying fear learning, especially those involving the amygdala. Amygdala activity is also upregulated by stress. Recently, however, a separate pathway has been proposed for interoceptive panic and anxiety signals, as patients exhibited CO2-inhalation induced panic responses despite bilateral lesions of the amygdala. This paradoxical observation has raised the possibility that cortical circuits may underlie these responses. We sought to examine these divergent models by comparing in vivo brain activation in unstressed and chronically-stressed rats breathing CO2. Regional cerebral blood flow measurements using functional Magnetic Resonance Imaging (fMRI) in lightly-anaesthetized rats showed especially strong activation of the somatosensory cortex by CO2 inhalation in the unstressed group. Strikingly, prior exposure to chronic stress occluded this effect on cortical activity. This lends support to recent clinical observations and highlights the importance of looking beyond the traditional focus on limbic structures, such as the hippocampus and amygdala, to investigate a role for cortical areas in panic and anxiety in humans.